The Nude in Art. - Simmins, Richard B. (Vancouver : Vancouver Art Gallery, 1964)
Cézanne, Paul ; Degas, Edgar ; Rodin, Auguste ; Corinth, Lovis ; Maillol, Aristide ; Matisse, Henri ; Villon, Jacques ; Brancusi, Constantin ; Léger, Fernand ; Picasso, Pablo ; Lachaise, Gaston ; Braque, Georges ; Modigliani, Amedeo ; Laurens, Henri ; Archipenko, Alexander ; Chagall, Marc ; etc.
The Nude in Art, Vancouver Art Gallery, Vancouver, November 3-29, 1964
English
kunstcatalogus